A Madea Christmas [videorecording (DVD)] : the movie - Perry, Tyler; Perry, Tyler; Horsford, Anna Maria; Sumpter, Tika; Witt, Alicia, 1975- (Lionsgate Entertainment Inc., 2014)
Madea gets coaxed into helping a friend pay her daughter a surprise visit in the country for Christmas, but the biggest surprise is what they'll find when they arrive. As the small, rural town prepares for its annual Christmas Carnival, new secrets are revealed and old relationships are tested while Madea dishes her own brand of Christmas Spirit to all.